Leonardo da Vinci - Rich, Richard; Brown, Jared F.; Nissen, Brian, 1939-; Stephens, Laurie Bonnell; Nest Entertainment, Inc.; Rich Animation Studios (Coppell, TX : NEST Family Entertainment, 2005)
Animated biography of Leonardo da Vinci, master painter, celebrated artist , and brilliant inventor..
"Interactive DVD packed with bonus features" -- Container.
Website access feature requires a computer with DVD drive and Internet access. Computer is not required for other DVD-video bonus features" -- Container.
Includes Resource & Activity Book.
Produced & directed by Richard Rich ; executive producer, Jared F. Brown ; screenplay, Brian Nissen ; music, Lex De Azevedo.
DVD format.
Includes Spanish language track with optional English or Spanish subtitles.
Keywords: Leonardo, -- da Vinci, -- 1452-1519 -- Video recordings; DVDs